The Importance of Demography in Social Sciences - Khababa, Nourredine; Bengana, Ismail; Mili, Khaled; Brika, Said Khalfa (Journal of Posthumanism, 2025)
Demography is considered one of the most important social sciences, especially since it is related to humans and their needs in light of the scarcity of economic resources. It consists of a set of theories that explain to us the reasons for the development of societies and their increase, and the models with their mathematical formulas measure their numbers and estimate their numbers in the future, while the policies represent the practical side that governments take to take appropriate measures to control their numbers, whether through expansionary or contractionary policies, according to the necessity that officials and experts see for each country.